Tragopogon turcicus sp. nov. (Asteraceae) from Turkey and its phylogenetic position. (26th July 2015) - Gültepe, Mutlu; Coşkunçelebi, Kamil; Makbul, Serdar; Sağlam, Coşkun
<x xml:space="preserve">Abstract</x> Tragopogon turcicus Coşkunç., M.Gultepe & Makbul, a new diploid species (2n = 2x = 12), is described and illustrated from Kızıldağ National Park (Isparta), southwest Anatolia. It is morphologically similar to T. oligolepis Hartvig & Strid which is also endemic to Turkey. Diagnostic characters, description, conservation status together with micro‐ and macro‐morphological properties of achenes and pollen grains are given. A phylogenetic analysis based on nrDNA ITS sequence data indicated that T. oligolepis is the sister species of the new taxon.